Large Friable Rectal Neuroendocrine Tumor Complicated by Hemorrhagic Shock: A Rare Case Report and Review of the Literature - Yazan Abboud; Imran Qureshi; Ayham Khrais; Alexander Le; Param Patel; Ozlem Fidan Ozbilgin; Sima Vossough‐Teehan (JGH Open)
ABSTRACT Rectal neuroendocrine tumors (NETs) are rare neoplasms that are usually asymptomatic and diagnosed incidentally. There are limited data on the presentation and management of high‐grade poorly differentiated large friable rectal NETs. We report the first case of an 87‐year‐old male who presented with chronic diarrhea and subsequently had severe hematochezia complicated by hemorrhagic shock and cardiac arrest and was diagnosed with a 7‐cm high‐grade friable rectal NET. Our case sheds light on the need to consider NETs in cases of chronic diarrhea and on the importance of endoscopy‐guided biopsy in the diagnosis and categorization, which can guide management.